Impact of LOC, Conservation and Social Support on Mental Health - Sinha, Kumari Bharti (Journal of Advanced Research in Journalism & Mass Communication, 2020)
This abstract deals with the impact of LOC [Locus of Control], conservatism and social support on mental health. For this a study was done. The study was conducted on 160 respondents to examine the effect of locus of control, conservatism and social support on mental health. It was hypothesized that locus of control, conservatism and social support would have a significant influence on mental health. For the purpose, MMHSI by Thakur and Kumar, Hindi version of Rotter’s Locus of Control Scale by Hasnayan and Joshi, Mohsin’s C-Scale, Social Support Scale by Asthana and Verma along with PDS were used to measure mental status of the respondents respectively. The obtained data were analysed using t-test. How to cite this article: Sinha KB. Impact of LOC, Conservation and Social Support on Mental Health. J Adv Res Jrnl Mass Comm 2020; 7(1): 1-3. DOI: https://doi.org/10.24321/2395.3810.202001